2024
DOI: 10.3390/ijms25063133
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Silk-Based Particulate Systems for the Controlled Release of Pharmaceuticals and Bioactive Agents in Wound Healing and Skin Regeneration

Beatriz G. Bernardes,
Anabela Veiga,
Joana Barros
et al.

Abstract: The increasing demand for innovative approaches in wound healing and skin regeneration has prompted extensive research into advanced biomaterials. This review focuses on showcasing the unique properties of sustainable silk-based particulate systems in promoting the controlled release of pharmaceuticals and bioactive agents in the context of wound healing and skin regeneration. Silk fibroin and sericin are derived from well-established silkworm production and constitute a unique biocompatible and biodegradable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 162 publications
(314 reference statements)
0
3
0
Order By: Relevance
“…These chains connect via a single disulfide bridge and a glycoprotein called P25 (with a molecular weight of 25.4 kDa). 2 SF has been used for centuries as a suture material as a result of its smooth texture, strength, and low immunogenicity. Over the last decades, this fibrous protein has been considered a well-established material for biomedical engineering due to its versatility and mechanical strength, used in the development of stable scaffolds, hydrogels, and fibers.…”
Section: Olivia Fostermentioning
confidence: 99%
See 1 more Smart Citation
“…These chains connect via a single disulfide bridge and a glycoprotein called P25 (with a molecular weight of 25.4 kDa). 2 SF has been used for centuries as a suture material as a result of its smooth texture, strength, and low immunogenicity. Over the last decades, this fibrous protein has been considered a well-established material for biomedical engineering due to its versatility and mechanical strength, used in the development of stable scaffolds, hydrogels, and fibers.…”
Section: Olivia Fostermentioning
confidence: 99%
“…SS has been reported as biocompatible with antioxidant and moisturizing properties. 1,2 For several decades, SS has been associated with immunogenicity and cytotoxicity due to inadequate extraction and purification processes resulting in the presence of impurities or residues from the silk fibers or inadequate removal of chemicals after extraction. 33 Recently, it has been reported that SS extracted by heat, acid, and alkaline solution is non-toxic to cells at concentrations up to 100 mg mL À1 .…”
Section: Propertiesmentioning
confidence: 99%
“…These properties of SF not only ensure its safety and efficacy in clinical applications, but also provide a multifunctional platform for the encapsulation and distribution of a wide range of therapeutic agents. 126 Through engineering modifications, SF can be further optimized to meet specific medical needs, such as improving drug stability, enhancing targeting capabilities, or modulating drug release received the most attention for tissue rejuvenation utilization. In particular, TE loading of growth factors into SF scaffolds for bone and cartilage has been proposed, dynamics, thereby enhancing therapeutic efficacy and reducing potential side effects.…”
Section: Applicationsmentioning
confidence: 99%